Differing Responses to Phytophthora cinnamomi Infection in Susceptible and Partially Resistant Persea americana (Mill.) Rootstocks: A Case for the Role of Receptor-Like Kinases and Apoplastic Proteases - Backer, Robert; Engelbrecht, Juanita; van den Berg, Noëlani (Frontiers in Plant Science, 2022)
The hemibiotrophic plant pathogen Phytophthora cinnamomi Rands is the most devastating pathogen of avocado (Persea americana Mill.) and, as such, causes significant annual losses in the industry. Although the molecular basis of P. cinnamomi resistance in avocado and P. cinnamomi virulence determinants have been the subject of recent research, none have yet attempted to compare the transcriptomic responses of both pathogen and host during their interaction. In the current study, the transcriptomes of both avocado and P. cinnamomi were explored by dual RNA sequencing. The basis for partial resistance was sought by the inclusion of both susceptible (R0.12) and partially resistant (Dusa®) rootstocks sampled at early (6, 12 and 24 hours post-inoculation, hpi) and late time-points (120 hpi). Substantial differences were noted in the number of differentially expressed genes found in Dusa® and R0.12, specifically at 12 and 24 hpi. Here, the partially resistant rootstock perpetuated defense responses initiated at 6 hpi, while the susceptible rootstock abruptly reversed course. Instead, gene ontology enrichment confirmed that R0.12 activated pathways related to growth and development, essentially rendering its response at 12 and 24 hpi no different from that of the mock-inoculated controls. As expected, several classes of P. cinnamomi effector genes were differentially expressed in both Dusa® and R0.12. However, their expression differed between rootstocks, indicating that P. cinnamomi might alter the expression of its effector arsenal based on the rootstock. Based on some of the observed differences, several P. cinnamomi effectors were highlighted as potential candidates for further research. Similarly, the receptor-like kinase (RLK) and apoplastic protease coding genes in avocado were investigated, focusing on their potential role in differing rootstock responses. This study suggests that the basis of partial resistance in Dusa® is predicated on its ability to respond appropriately during the early stages following P. cinnamomi inoculation, and that important components of the first line of inducible defense, apoplastic proteases and RLKs, are likely to be important to the observed outcome.